The Use of Simple Antiseptics and Disinfectants to Prevent Viral Infections - Islomov Akmal Khushvaktovich; Kurbanova Aypara Djoldasovna; Komilov Kamaridin Urinovich (Genius Publishing Group, 2021)
The given article provides insights into infections, viruses, and antiseptics and disinfectants, as well as chemicals that have antimicrobial effects. In addition, this article elucidates the methods of preparation of the chemicals with antiseptic and disinfectant properties which are widely used as antiseptics and disinfectants, easy to obtain and prepare, inexpensive, simple, popular, harmless, also has strong anti-parasitic effect, against various viral infectious diseases in the prevention and eradication of various viral infectious diseases.
Keywords: Infection; virus; antiseptic; disinfectant